A Perspective on Chronic and Long-Lasting Anorexia Nervosa - Speciani, Maurizio; Barak, Yoram; Damanhuri, Hanafi; De Ronchi, Diana; Panariello, Fabio; Atti, Anna Rita (Frontiers in Psychiatry, 2021)
Anorexia Nervosa (AN) is a severe eating disorder which typically develops in younger females. Many studies focus on this specific population, a majority of which will eventually partially or fully recover. A minority will become chronic despite extensive treatment. These patients are treatment-resistant and may not necessarily benefit from usual treatment. In this article we will reflect on possible mechanisms which may explain the maintenance of disease, and especially on the possible role of affective and anxiety disturbances. We will use, due to the lack of large-scale studies, data from risk and prognostic factors, treatment options and neurobiological correlates in chronic AN patients. Lastly, we will propose how these elements may advise further research and treatments.